DECISION SUPPORT SYSTEM SELEKSI KARYAWAN OFFICE DEPARTEMENT MENGGUNAKAN METODE TECHNIQUE FOR OTHERS REFERENCE BY SIMILARITY TO IDEAL SOLUTION (TOPSIS) - azimaturrafi'ah -; Umi Chotijah; Henny Dwi Bhakti (Universitas Muhammadiyah Gresik, 2021)
ABSTRACT Employees are people who provide services to companies or organizations that require labor services, from which the employees will receive remuneration in the form of salaries and other compensations. PT. Tenaco Jaya Langgeng Abadi is a company that produces in the field of piping, steel structure, and engineering. This company has problems in the performance of office department employees, so the researchers wrote research on decision support systems for office department employee selection using the technique for others reference by similarity to ideal solution (topsis) methods to assist HRD in determining the selection of office department employees. This system will rank employees using the topsis method, from this ranking HRD will select 5 employees with the lowest scores who will attend training from the company. There are 5 weight characteristics of this research, namely: Skill, Age, office application, Greafis Design, and Trobel Hardware. Skill, Age, office application, Greafis Design, and Trobel Hardware. TOPSIS has a concept where the chosen alternative is the best alternative that has the shortest distance from the positive ideal solution and the farthest distance from the negative ideal solution. The more factors that must be considered in the decision-making process, the more difficult it is to make a decision on a problem. Keywords: decision support system, office department employee selection, topsis method